Akt pathway is hypoactivated by synergistic actions of diabetes mellitus and hypercholesterolemia resulting in advanced coronary artery disease - Hamamdzic, Damir (American Physiological Society, 2010)
Atherosclerosis is an inflammatory process leading to enhanced cellular proliferation, apoptosis, and vasa vasorum (VV) neovascularization. While both diabetes mellitus (DM) and hypercholesterolemia (HC) predispose to atherosclerosis, the precise interaction of these risk factors is unclear. Akt is a central node in signaling pathways important for inflammation, and we hypothesized that DM/HC would lead to aberrant Akt signaling and advanced, complex atherosclerosis. DM was induced in pigs by streptozotocin and HC by a high-fat diet. Animals were randomized to control (non-DM, non-HC), DM only, HC only, and DM/HC groups. Coronary artery homogenates were analyzed by immunoblotting for proteins involved in the Akt pathway, including phosphorylated (p)-Akt (Ser473), p-GSK-3β (Ser9), activated NF-κB p65, and VEGF. Immunohistochemical staining for Ki67 (cell proliferation), terminal deoxynucleotidyltransferase-mediated dUTP nick end labeling (TUNEL) (apoptosis), and von Willebrand factor (vWF) (neovascularization) was performed. Neovascularization was visualized with micro-computerized tomography (CT). Only DM/HC animals developed advanced atherosclerosis and showed decreased p-Akt (Ser473) and p-GSK-3β (Ser9) levels (P < 0.01 and P < 0.05, respectively). DM/HC arteries demonstrated increased cellular proliferation (P < 0.001), apoptosis (P < 0.01), and activation of NF-κB p65 (P < 0.05). Induction of DM/HC also resulted in significant VV neovascularization by enhanced VEGF expression (P < 0.05), increased vWF staining (P < 0.01), and increased density by micro-CT. In conclusion, DM and HC synergistically resulted in complex atherosclerosis associated with attenuated p-Akt (Ser473) levels. Aberrant Akt signaling correlated with increased inflammation, cellular proliferation, apoptosis, and VV neovascularization. Our results revealed a synergistic effect of DM and HC in triggering abnormal Akt signaling, resulting in advanced atherosclerosis.